The effects of COVID-19 Pandemic on the Psyche and Productivity of Pharmaceutical Sales Workforce in an African Country; A descriptive case study: The effects of COVID-19 Pandemic on a Sales Workforce - OAMEN, Theophilus Ehidiamen (Advances in Social Sciences Research Journal, 2021)
Pharmaceutical sales representatives are a pivotal workforce in the healthcare system. Due to the global impact of COVID-19, the impact on the psyche and morale of the pharmaceutical sales workforce has to be examined. The primary objective of the study was to assess the possible impact of the COVID-19 pandemic on the psyche and productivity of the pharmaceutical sales workforce in Nigeria. A questionnaire-guided cross-sectional survey was used to collect data from pharmaceutical sales personnel across the six geopolitical zones in Nigeria using purposive sampling. The final sample was 225. Statistical analysis was done using SPSS 25. Descriptive statistics such as mean, standard deviation were used for demographic data. Cluster analysis was used to identify key demographic predictors of importance. X2 test was used to test the association between the sociodemographic characteristics of respondents and work-attributes. The difference of means was determined with a t-test. Highest and lowest-ranked work-attributes were information provider (3.62±1.36), and involvement in COVID screening activities (1.80±1.20). Average daily work hours before and during COVID-19 lockdown (2.16±0.04 vs. 1.88±0.11, p<0.05)) were affected. Average sales were significantly affected (3.15±0.48 vs. 1.35±0.36, p<0.0001). Psychological states of Anxiety and Increased burden have a medium to high impact on the psyche of respondents. The study revealed an association of both extremes of pessimism and optimism with regards to Frustration state of mind. Study suggests an overall negative impact on pharmaceutical sales representatives’ psyche and productivity. Attention to sales workforce welfare is required to safeguard medicine supply.